Illocutionary Acts in Retno Marsudi’ Speech at the General Debate of the 78th Session of the United Nations General Assembly - Putri, Rossa Dwi Nova; Prastikawati, Entika Fani; Hawa, Faiza (Universitas Negeri Semarang, 2024)
This study focuses on analyzing the illocutionary acts present in Retno Marsudi’s speech during the general debate of the 78th session of the United Nations General Assembly. This study aims to describe the types of illocutionary acts employed, discerning the most and least frequent types as well as their implications. The data were analyzed by the descriptive qualitative method, and collected by finding out the video, watching the video, transcribing the speech video, and then identifying the data that were related to the theory. The writers used Searle’s theory for the types of illocutionary acts, which categorizes illocutionary acts into five types: representative, directive, commissive, expressive, and declarative. The findings from the study revealed that there are a total of 87 data points found in the speech, with directive acts being the most dominant with a total of 37 (42,5%), followed by representative at 27 (31%), commissive at 13 (15%), declarative at 6 (6,9%), and expressive being the least dominant at 4 (4,6%). The findings indicate that directive acts are primarily used to convey urgent messages and prompt action, while expressive acts are the least dominant, reflecting Retno Marsudi’s emphasis on advocating for action rather than expressing personal emotions or attitudes.